A Combination of Podophyllotoxin and Rutin Alleviates Radiation-Induced Pneumonitis and Fibrosis through Modulation of Lung Inflammation in Mice - Verma, Savita; Kalita, Bhargab; Bajaj, Sania; Prakash, Hridayesh; Singh, Ajay Kumar; Gupta, Manju Lata (Frontiers in Immunology, 2017)
Pneumonitis and pulmonary fibrosis are predominant consequences of radiation exposure, whether planned or accidental. The present study, demonstrates radioprotective potential of a formulation, prepared by combining podophyllotoxin and rutin (G-003M), in mice exposed to 11Gy thoracic gamma radiation (TGR). Treated mice were observed for survival and other symptomatic features. Formation of reactive oxygen species (ROS)/nitric oxide (NO) was measured in bronchoalveolar lavage cells. DNA damage and cell death was assessed in alveolar cells by TUNEL assay. Total protein (TP), lactate dehydrogenase (LDH) and alkaline phosphatase (ALP) were measured in bronchoalveolar lavage fluid (BALF)/serum of mice to assess lung vascular permeability. Interleukin-6 (IL-6), tumor necrosis factor-α (TNF-α), transforming growth factor-β1 (TGF-β1)], CD45 (cluster of differentiation 45), inducible nitric oxide synthase (iNOS) and nitrotyrosine were also estimated in lungs/BALF of differentially treated mice. Our observations revealed 100% survival in G-003M pretreated mice against 66.50% in 11Gy TGR exposed. Other symptoms like reduction in greying of hair, weight loss and breathing rate were also observed in pretreated groups. Significant decline in reactive oxygen species (ROS)/nitric oxide (NO) and cell death in formulation pretreated mice was also observed. Decreased level of TP, LDH and ALP in BALF/serum samples revealed G-003M-induced inhibition in lung permeability. Level of IL-6, TNF-□□, TGF-β1 in the lungs of these mice was found corresponding to control group at 8 weeks post treatment. On the contrary, these cytokines raised significantly in 11Gy TGR exposed mice. Lung pneumonitis and fibrosis was found significantly countered in these mice. The observations revealed that G-003M could regulate immune system by curtailing radiation-induced oxidative and inflammatory stress which has helped in minimizing radiation-inflicted pneumonitis and fibrosis.